2011
DOI: 10.1097/aud.0b013e3181fa5da2
|View full text |Cite
|
Sign up to set email alerts
|

Do “Optimal” Conditions Improve Distortion Product Otoacoustic Emission Test Performance?

Abstract: Objectives To determine whether an “optimal” DPOAE protocol including (1) optimal stimulus levels and primary-frequency ratios for each f2, (2) simultaneously measuring 2f2-f1 and 2f1-f2 distortion products, (3) controlling source contribution, (4) implementing improved calibration techniques, (5) accounting for the influence of middle-ear reflectance, and (6) applying multivariate analyses to DPOAE data results in improved accuracy in differentiating between normal-hearing and hearing-impaired ears, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The extent of transmission of sounds through the TM at certain frequencies could therefore be more predictive of test performance than standing-wave effects. However, this hypothesis was not supported by Kirby et al (2011), who found no correlation between reflectance and DPOAE test performance.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…The extent of transmission of sounds through the TM at certain frequencies could therefore be more predictive of test performance than standing-wave effects. However, this hypothesis was not supported by Kirby et al (2011), who found no correlation between reflectance and DPOAE test performance.…”
Section: Discussionmentioning
confidence: 40%
“…Although calibration errors were evident at other frequencies, the distribution of error magnitudes does not provide an explanation for the poorer test performance at 8 kHz in the Burke et al study. However, the results of Scheperle et al (2008) and Kirby et al (2011) suggest value in continuing to explore FPL as an alternative method of calibration for DPOAEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rogers et al (2010) failed to demonstrate that FPL calibration improved threshold predictions. In contrast, Kirby et al (2011) found a significant improvement in test performance when FPL calibration was used; however, the calibration method was paired with optimized stimulus levels, and the sources of improvement could not be examined independently.…”
Section: Introductionmentioning
confidence: 85%
“…Several investigators have tested whether the theoretical advantages of quantifying ear-canal sound level in FPL are apparent empirically using distortion product otoacoustic emissions (DPOAE) or behavioral thresholds as outcome measures (DPOAEs: Scheperle et al, 2008;Burke et al, 2010;Rogers et al, 2010;Kirby et al, 2011. Behavioral Thresholds: Withnell et al, 2009McCreery et al, 2009;Lewis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%